HAK ATAS RUANG DALAM DISKURSUS AWE-AWE - Agung Dharma Yuda Adi Ramadhan; Tiara Yulita Sari; Septian Rahmat Purnomo (Jurnal Ilmiah Sosiologi Agama (JISA), 2023)
Awe-awe is a term for those who have the job of being a road guide for vehicles passing through the Gumitir route, Banyuwangi Regency. The steep road conditions in the Gumitir route area make awe-awe seem to be very much needed. Where this makes awe-awe activities widely practiced by the surrounding community. Initially, the awe-awe was tasked with helping and giving signals to vehicles that were about to pass the bend. However, awe-awe developed into a medium for begging and became a tradition that was passed down to the next generation. The complexity of the awe-awe phenomenon occurs when there is a privatization of space by the power elite which causes a reduction in freedom to do awe-awe. This research uses the perspective of Space theory proposed by Henri Lefebvre. According to Lefebvre, spatial space in modern capitalist society is a battleground that will never end. The purpose of this research is to find out the complexity of the lives of awe-awe actors in the contemporary era which has been colored by capitalist domains and privatization of space so that it has an impact on the lack of fulfillment of space rights by awe-awe actors. The type of research is qualitative research with an ethnographic approach. The results showed that there has been the privatization of space in the Gumitir path area due to the process of land capitalization by the community and local government. This privatization of space also has an impact on the non-fulfillment of the space for awe-awe actors, which over time the meaning of awe-awe has shifted by adjusting the situation and conditions of the existing reality.